2011
DOI: 10.1007/s00253-011-3441-x
|View full text |Cite
|
Sign up to set email alerts
|

LC-PUFA from photosynthetic microalgae: occurrence, biosynthesis, and prospects in biotechnology

Abstract: Microalgae offer potential for numerous commercial applications, among them the production of long-chain polyunsaturated fatty acids (LC-PUFAs). These valuable fatty acids are important for a variety of nutraceutical and pharmaceutical purposes, and the market for these products is continually growing. An appropriate ratio of LC-PUFA of the ω-3 and ω-6 groups is vital for "healthy" nutrition, and adequate dietary intake has strong health benefits in humans. Microalgae of diverse classes are primary natural pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
105
0
3

Year Published

2012
2012
2020
2020

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 181 publications
(109 citation statements)
references
References 115 publications
1
105
0
3
Order By: Relevance
“…The main source of n-3 FA for human consumption is fish oil (Turchini et al 2012). However, fish do not produce high amounts of these FAs but obtain them in their diet from the primary producers of n-3 PUFA which are microalgae (Harel et al 2002;Atalah et al 2007;Khozin-Goldberg et al 2011;Turchini et al 2012).…”
Section: Introductionmentioning
confidence: 99%
“…The main source of n-3 FA for human consumption is fish oil (Turchini et al 2012). However, fish do not produce high amounts of these FAs but obtain them in their diet from the primary producers of n-3 PUFA which are microalgae (Harel et al 2002;Atalah et al 2007;Khozin-Goldberg et al 2011;Turchini et al 2012).…”
Section: Introductionmentioning
confidence: 99%
“…They are known as the primary producers of a variety of long-chain polyunsaturated fatty acids (PUFAs) in aquatic environments and numerous studies have shown that nutraceutically important omega-3 (ω3) and omega-6 (ω6) PUFAs are quite abundant in microalgae (Otleş and Pire 2001, Bigogno et al 2002, Ikawa 2004, Patil et al 2007, Khozin-Goldberg et al 2011. As the global ω3 and ω6 PUFAs market is expanding at a remarkable rate, microalgae have gained considerable attention as an alternative source to fish oil due to their fast growth rate and high PUFA contents (Seto et al 1984, Benemann et al 1987.…”
Section: Introductionmentioning
confidence: 99%
“…Research on lipid metabolism in microalgae has flourished in recent years due to their potential as a rich source of v-3 fatty acids (Guschina and Harwood, 2006;Khozin-Goldberg et al, 2011) and as a feedstock for biodiesel (Hu et al, 2008b;Rosenberg et al, 2008;Beer et al, 2009;Radakovits et al, 2010;Wijffels and Barbosa, 2010;Merchant et al, 2012;Work et al, 2012). Oils produced by microalgae resemble that of plants (Hu et al, 2008b), with the exception that they contain higher proportions of polyunsaturated fatty acid (PUFA) species (Harwood and Guschina, 2009).…”
mentioning
confidence: 99%